2011
DOI: 10.1002/jcp.22447
|View full text |Cite
|
Sign up to set email alerts
|

Substance P stimulates the recovery of bone marrow after the irradiation

Abstract: The therapeutic use of ionizing radiation (e.g., X-rays and γ-rays) needs to inflict minimal damage on non-target tissue. Recent studies have shown that substance P (SP) mediates multiple activities in various cell types, including cell proliferation, anti-apoptotic responses, and inflammatory processes. The present study investigated the effects of SP on γ-irradiated bone marrow stem cells (BMSCs). In mouse bone marrow extracts, SP prolonged activation of Erk1/2 and enhanced Bcl-2 expression, but attenuated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…Furthermore, SP also -sue injury, as shown in radio-induced BM and gastro-intestinal (GI) damages (Kang et al, 2009;Kim et al, , 2010An et al, 2011) and spinal cord injury (Jiang et al, 2012(Jiang et al, , 2013. Multifunctional effects of SP in the process of wound healing propose the SP-peptide as a candidate -ease as well as facilitating tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, SP also -sue injury, as shown in radio-induced BM and gastro-intestinal (GI) damages (Kang et al, 2009;Kim et al, , 2010An et al, 2011) and spinal cord injury (Jiang et al, 2012(Jiang et al, , 2013. Multifunctional effects of SP in the process of wound healing propose the SP-peptide as a candidate -ease as well as facilitating tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…It is worthy of note that pretreatment to cultured human mesenchymal stem cells with SP led to a decrease in apoptotic cells after irradiation (101), implying the potential therapeutic use of SP pretreatment in minimizing radiation damage to patients.…”
Section: Tks and Hematopoiesismentioning
confidence: 99%
“…Moreover, SP causes the mobilization of bone marrowderived stem cells to participate in corneal wound healing (19,20). Interestingly, recent evidences have shown that SP activates the EGFR, mitogen-activated protein kinases (MAPKs), extracellular signal-regulated kinases (ERKs), and phosphoinositide 3-kinase-Akt (PI3K-Akt) signaling pathways, as well as promotes the healing of inflamed colonic epithelium (21) and possesses antiapoptotic effects in colonocytes (22), dendritic cells (23), tenocytes (24), neutrophils (25), and bone marrow-derived stem cells (26).…”
mentioning
confidence: 99%